Effect of ice hockey stick stiffness on performance - Kays, B. T.; Smith, L. V. (Sports Engineering, 2017)
Hockey sticks have undergone a dramatic transformation from wood to aluminum to composite in just over the past 20 years. With the introduction of different materials, there has been increasing interest in how the material properties affect shot speed. This study examined the effects of stick stiffness from measured swing motion on puck speed. Stick evaluation involved a six amateur player study, quasi-static stiffness measurement, video motion analysis, and numerical simulation. The effect of stiffness on puck speed was observed to depend on shot type. For shots involving large stick loading, as occurs with a slap shot, puck speed decreased as stick stiffness increased. The trend was consistent with a constant force player model. For shots involving low stick loading, as occurs with a wrist shot, puck speed increased as stick stiffness increased. The trend was consistent with a constant displacement player model. Finite element simulation of the slap shot agreed generally with the results of the player study and was used to find an optimal loading distance (distance that the stick contacts the ice prior to the puck) to be 24 cm.